Modern methods of the crime of terrorism in domestic and international laws - Alsulami, Amnah Mulfi (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to explain the international and internal efforts to enact laws to combat the crime of terrorism in its modern forms and limit its effects, by developing legislation that criminalizes these forms with their different types and methods used in committing them in a manner commensurate with the modern era, despite their diversity, development and widespread. This study dealt with the concept of terrorism according to international laws and agreements, its motives that lead to its perpetration in societies, and its impact on people’s behavior, whether stemming from a belief or the result of an economic situation, as well as modern images of terrorism and the efforts of states and the international community to combat it and approve legislation that is commensurate with the modernity of this crime. The study concluded that the crime of terrorism is not new to society, but rather it is renewed and its patterns change with different times and eras, and that the laws that were put in place to combat it have had an effective role in reducing it, but they still need some changes to thwart it and work to eradicate it by approving regional laws that criminalize acts that It would form the basis of terrorist activity.